2019
DOI: 10.1080/14786419.2019.1593165
|View full text |Cite
|
Sign up to set email alerts
|

New derivatives of 11-keto-β-boswellic acid (KBA) induce apoptosis in breast and prostate cancers cells

Abstract: A series of new 11-keto-β-boswellic acid were partially-synthesized by modifying the hydroxyl and carboxylic acid functional groups of ring A. The structures of the new analogs were confirmed by detailed spectral data analysis. Compounds 4, 5 and 9 exhibited potent anti-cancer results against two human tumor cancer cell lines having IC 50 value of MCF-7 (breast) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…10,11 Recently, AKBA was also found to exhibit antitumor effects in human cell lines established from prostate cancer, breast cancer and glioblastoma. [12][13][14] Csuk et al demonstrated that boswellic acid and its derivatives induce apoptosis in breast and cervical cancers cells. 15 Liu indicated that AKBA inhibits the proliferation and cancer stem cell-like properties of docetaxel resistant prostate cancer cells in vitro and in vivo via blocking Akt and Stat3 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recently, AKBA was also found to exhibit antitumor effects in human cell lines established from prostate cancer, breast cancer and glioblastoma. [12][13][14] Csuk et al demonstrated that boswellic acid and its derivatives induce apoptosis in breast and cervical cancers cells. 15 Liu indicated that AKBA inhibits the proliferation and cancer stem cell-like properties of docetaxel resistant prostate cancer cells in vitro and in vivo via blocking Akt and Stat3 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, boscartin M, isoincensole oxide, incensole oxide, and incensole oxide acetate had a mild hepatoprotective effect at 10 μM [25]. In the other report by Wang et al, the investigation of B. sacra led to the isolation of ten new cembrane-type diterpenes, including boscartins AL-AU (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and five known analogs (35)(36)(37)(38)(39). Moreover, biological evaluations revealed that compounds 27, 29, 36, and 37 displayed hepatoprotective activities against paracetamol-induced HepG2 cell damage at 10 μM.…”
Section: Diterpenoidsmentioning
confidence: 97%
“…One of the important uses of BAs in medicine is as an anti-inflammatory. Boswellic acids suppress leukotriene biosynthesis in neutrophilic granulocytes by nonredox, noncompetitive inhibition of 5-lipoxygenase [32,[35][36][37]. e pharmacological effects of B. sacra extract are commonly explained by the presence of boswellic acids [36].…”
Section: Boswellic Acids Andmentioning
confidence: 99%
“…These aconitine alkaloids, including aconine, songorine and neoline, showed less toxicity but higher analgesic (Dong et al, 2015; Suzuki et al, 2016; Tanimura, Yoshida, Ishiuchi, Ohsawa, & Makino, 2019) and anti‐inflammatory activities (Qi et al, 2018; Wang et al, 2019; Zhang et al, 2015). KBA and AKBA, the representative pentacyclic triterpenic acid in Boszvellia carterii Birdw , showed strongly anti‐inflammatory (Bini Araba et al, 2019; Goel, Ahmad, Singh, & Singh, 2010; Ranzato et al, 2017) and anti‐tumour activities (Sayed & El Sayed, 2016; Takahashi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%